The Limits of the Anthropocene: Anticolonial Humanity in Kidlat Tahimik's Mababangong Bangungot and Souleymane Cissé's Yeelen. Issue 7 (3rd October 2022) - Bouchard, Danielle
Abstract : Recently, many authors have dismissed critical frameworks such as the postcolonial as inadequate for confronting the humanity-imperiling problems of the Anthropocene. But this dismissal is itself a reiteration of the racist and indeed genocidal logics so thoroughly critiqued within postcolonial and allied anticolonial frameworks. This essay thus revisits two films made before the rise of Anthropocene discourse, which exemplify the kind of work that has long understood the perils to humanity of a colonial world order: Kidlat Tahimik's Mababangong Bangungot (Philippines 1977) and Souleymane Cissé's Yeelen (Mali 1987). I break with the tendency to understand these films' aesthetic features largely in relation to the local cultural forms and practices they portray. Rather, I consider how they engage the aesthetic toward an anticolonial critique of contemporary geopolitics, namely, by offering analyses of development and nuclear colonialism, both central to post-World War II modes of imperial governance. These films offer the kind of critical engagement with colonialist, genocidal, and racist conceptions of humanity which the framework of the Anthropocene has largely been unable to provide .